The psychology of women and gender half the human experience - Else-Quest, Nicole; Hyde, Janet Shibley (SAGE, 2018)
With clear, comprehensive, and cutting-edge coverage, The Psychology of Women and Gender: Half the Human Experience + delivers an authoritative analysis of classical and up-to-the-minute research from a feminist, psychological viewpoint. Authors Nicole M. Else-Quest and Janet Shibley Hyde examine the cultural and biological similarities and differences between genders, noting how they are often a result of inequality. The Ninth Edition emphasizes rigorous methodology and reviewing and evaluating empirical evidence, helping demystify the scientific process in this field of study. Hands-on applications through case studies that integrate research from other disciplines give students further experience with key issues. This proven resource equips readers with a strong foundation for understanding the dynamic influences of gender, sexual orientation, and ethnicity in the context of psychology and society, along with strategies for thinking critically about popular culture and using psychological science to improve people’s lives and promote gender equality.--Provided by publisher.